Quercetin improves immune function in Arbor Acre broilers through activation of NF-κB signaling pathway - Yang, J.X. (Poult Sci, 2020)
Quercetin, the main component of flavonoids, has a wide range of biological actions. Quercetin can be made into a variety of additives for practice, because of the stable chemical structure and water-soluble derivatives. This study was intended to explore the effects of quercetin on immune function and its regulatory mechanism in Arbor Acre broiler to provide a practical basis for improving poultry immune function and figure out the optimum supplementation as functional feed additives. A total of 240 one-day-old healthy Arbor Acre broilers, similar in body weight, were randomly allotted to 4 treatments with 6 replicates, 10 broilers in each replicate and fed with diets containing quercetin at 0, 0.02, 0.04, and 0.06% for 6 wk. Blood and immune organs (spleen, thymus, and bursa) were collected from chickens at the end of the experiment. Growth performance, immune organs indexes, contents of serum immune molecules, splenic T lymphocyte proliferative responses, and expression of immune related genes were evaluated. The results showed that dietary quercetin had no significant effect (P > 0.05) on growth performance of broilers. Compared with control, 0.06% quercetin supplementation in diet significantly increased spleen index and thymus index (P < 0.05). It also increased the secretion of immune molecules including immunoglobulin A (IgA), interleukin-4 (IL-4) (P < 0.001), immunoglobulin M (IgM) (P = 0.007), complement component 4 (C4) (P = 0.001), and tumor necrosis factor-α (TNF-α) (P < 0.05). On the other hand, 0.02% quercetin supplementation significantly increased complement component 3 (C3) (P < 0.05). Additionally, both 0.04 and 0.06% quercetin supplementation significantly increased expression of TNF-α, TNF receptor associated factor-2 (TRAF-2), TNF receptor superfamily member 1B (TNFRSF1B), nuclear factor kappa-B p65 subunit (NF-κBp65), and interferon-γ (IFN-γ) mRNA (P < 0.05), and expression of NF-κB inhibitor-alpha (IκB-α) mRNA were significantly decreased (P < 0.05). Thus, quercetin improved immune function via NF-κB signaling pathway triggered by TNF-α.